2013
DOI: 10.4103/2230-8598.109324
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B vaccine: Coverage and factors relating to its acceptance among health care workers of a tertiary care center in North India

Abstract: Hepatitis B vaccine: Coverage and factors relating to its acceptance among health care workers of a tertiary care center in North IndiaBackground: Hepatitis B infection is the major cause of acute and chronic liver disease, cirrhosis, and hepatocellular carcinoma worldwide and has long been recognized as an occupational hazard among health care workers. Thus, this study was planned to evaluate the coverage of hepatitis B vaccine and to study occupational, epidemiologic, and attitudinal factors in its acceptanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
18
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 14 publications
7
18
4
Order By: Relevance
“…(25) We found that HCWs who perceived the threat of getting bloodborne infections including hepatitis B at workplace were more likely to receive complete doses of hepatitis B vaccination as compared to those who had no perception of getting blood borne infection while at work. To the best of our knowledge no study has investigated this association among primary health care workers however the finding is consistent with studies from tertiary care hospitals in North India (20) and Republic of Georgia. (27) Also, the odds of hepatitis B vaccination were higher among HCWs with perceived benefits of hepatitis B vaccination as compared to the HCWs who lack perception regarding the benefits of Hepatitis B vaccination against preventing hepatitis B infection.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…(25) We found that HCWs who perceived the threat of getting bloodborne infections including hepatitis B at workplace were more likely to receive complete doses of hepatitis B vaccination as compared to those who had no perception of getting blood borne infection while at work. To the best of our knowledge no study has investigated this association among primary health care workers however the finding is consistent with studies from tertiary care hospitals in North India (20) and Republic of Georgia. (27) Also, the odds of hepatitis B vaccination were higher among HCWs with perceived benefits of hepatitis B vaccination as compared to the HCWs who lack perception regarding the benefits of Hepatitis B vaccination against preventing hepatitis B infection.…”
Section: Discussionsupporting
confidence: 67%
“…However, this association disappeared at the multivariable level. Possible explanation for this inverse association between age and vaccination at the univariate level could be the result of higher acceptability of hepatitis B vaccination among younger HCWs as also observed in India (20) and Brazil. (21) Also, in Pakistan some paramedical, nursing and medical schools of the private sector have recently introduced hepatitis B vaccination for the new entrants which might have resulted in higher vaccination rates among younger HCWs as compared to those aged 60 years and above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason mainly asserted for not being vaccinated was found to be negligence among physiotherapy students and lab technicians whereas dental and nursing students have forgotten to take vaccine. 41 In other study 56 the reason for being not vaccinated was also found to be negligence. The present study revealed that majority of them recapped needles after use, had accidental needle prick injuries, tested for hepatitis B virus infection after injuries; and consulted and treated by doctor amongst the positive participants till the time of survey.…”
Section: Discussionmentioning
confidence: 99%
“…Such policy decisions do have a positive impact on work efficiency of nurses by creating a sense of being protected. Lower level of hepatitis B vaccination among nurses was reported from studies conducted in Greece (63.25%) [18], Iran (89.6%) [19], South Africa (68%) [20], and India (44.8%) [21]. …”
Section: Discussionmentioning
confidence: 99%